A static force model to analyze the nuclear deformation on cell adhesion to vertical nanostructures. Issue 35 (25th August 2022) - Li, Nanxin; Jin, Kun; Chen, Tongsheng; Li, Xinlei
Abstract : A theoretical model was established to pursue the nuclear deformation during cell adhesion to the nanopillar array by analyzing the mechanical force balance. Abstract : Vertical nanostructures have been found to induce the deformation of the nuclear envelope during cell adhesion. However, there has been a lack of quantitative analysis of the influence of nanostructures morphology on the degree of nuclear deformation. Here, a theoretical model was proposed to investigate the mechanism of nuclear deformation by analyzing the mechanical force balance. Based on the established model, we analyzed the effects of the morphology of the nanopillar array on nuclear deformation and gave the quantitative relationship of the deformation depth of the nucleus with the pitch and radius of nanopillars. Our theoretical results seem to show broad agreements with experimental observations, which implies that the work can provide useful guidance to the design of nanostructures for biomedical applications.